Recent progress in MXene layers materials for supercapacitors: High‐performance electrodes. Issue 1 (15th June 2022) - Wang, Yitong; Wang, Yuhua
Abstract: In 2011, Gogotsi et al. discovered a new type of two‐dimensional transition metal carbides and nitrides, called MXenes, which have become a dazzling new star in the energy storage industry. MXenes are endowed with a series of fascinating properties due to their unique structures and tunable surface chemical functional groups. The application of MXenes in electrochemical energy storage has attracted special attention, especially showing great potential in supercapacitor applications. Compared with other materials, MXenes have high mechanical flexibility, high energy density, and good electrochemical performance, so they are especially suitable as electrode materials for supercapacitors. However, similar to other 2D materials, due to the strong van der Waals forces, MXene layers inevitably undergo stacking agglomeration, resulting in severe loss of electrochemically active sites. If the self‐stacking of MXenes layers can be effectively suppressed, their electrochemical performance will be enhanced. Structural optimization of MXenes and composite doping of MXenes with other materials are two strategies with significant effects. This review summarizes recent advances in MXene synthesis, fundamental properties, and composite materials, focusing on the latest electrochemical performance of MXene‐based electrodes/devices,  and puts forward the challenges and new opportunities that MXenes face in this emerging energy storage field. Abstract : MXene is a bright new star in the field of energy storage, and the application of MXene in supercapacitors has received special attention. This study summarizes the latest progress in MXene synthesis, basic properties, and composite materials, focusing on MXene‐based electrodes/devices and the latest electrochemical performance. It presents challenges and new opportunities for MXene in this future energy storage field.